Bond Strength of Repaired Composite Resin Restorations - Rodrigo Máximo de ARAÚJO (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2007)
Purpose: To evaluate the bond strength of direct composite resins and composite repairs, using 3 different commercial brands - GI: Palfique Estelite Ó (Tokuyama), GII: Filtek Z350 (3M/ESPE) and GIII: Te Econon (Ivoclar/Vivadent) - and the use of AdperTM Single Bond 2 (3M/ESPE) adhesive system at the base/repair interface. Method: Thirty conic bases (5 mm x 5 mm x 3 mm) of each commercial brand of composite resin were fabricated. All bases of each group were submitted to a thermocycling regimen of 20,000 cycles (5ºC to 55ºC ± 2ºC, for 30 s). The bases of each group were randomly assigned to 3 sub-groups, in which a combination of the commercial brands was performed for the repairs. The specimens were stored in distilled water at 37°C during 7 days and were thereafter tested in tensile strength in a universal testing machine (EMIC - MEM 2000) with 500 kgf load cell running at a crosshead speed of 1.0 mm/min until fracture. Data in MPa were submitted to ANOVA and Tukey’s test (5%).Results: The following results were found: GI: Palfique Estelite Ó (11.22±4.00 MPa), Te Econom (12.03±3.47 MPa) and Filtek Z350 (10.66±2.89 MPa); GII: Palfique Estelite Ó (8.88±2.04 MPa), Te Econom (7.77±1.64 MPa) and Filtek Z350 (10.50±6.14 MPa); and GIII: Palfique Estelite Ó (8.41±2.50 MPa), Te Econom (12.33±3.18 MPa) and Z350 (11.73±3.54 MPa).Conclusion: The bond strengths at the interface of the different composite resins submitted to repair were statistically similar regardless of the commercial brand.